Media Presentation Design of Railroad Crossing Discipline for Teenagers 15-18 Years Old by Indonesian Edan Sepur Community in Bandung - Meti Agni Rizkiani; Acep Suparman; Sophia Purbasari; Oky Mauludya; Citra Kemala Putri (Research Collaboration Community (RCC), 2023)
A railroad crossing is an intersection where a railway line crosses a road that can become an accident-prone point. The high number of accidents on a railroad crossing is due to the low level of society’s discipline in traffic. One of the communities who cares about this phenomenon is Edan Sepur Indonesia Community. There were 16.111 violations on 5 railroad crossings in Bandung for the last 6 months of the Crossing Discipline Event 2022. The purpose of this design is to make an interesting media presentation related to railroad crossing discipline that will be socialized to the teenagers aged 15-18 years old in Bandung. The method used on this design is a qualitative method by doing observation, interview and questionnaire. This media presentation design is aimed to provide knowledge and early education concerning the awarness of railroad crossing discipline to prevent accidents.